Каталітична активність вуглецевих наноматеріалів у реакції розкладання пероксиду лаурилу - Haliarnyk, D. M.; Brychka, D. S.; Bakalinska, O. M.; Kartel, M. T. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
The stability of lauroyl peroxide in toluene, carbon tetrachloride, dioxane, ethyl acetate and benzene was investigated. Catalytic activity of nanoporous (KAU and SKN) and nanoscale (CNT) carbon materials, their modified forms (oxygen- and nitrogencontaining) and enzyme catalase was determined by Michaelis constant calculation according to the kinetics of peroxide decomposition. It was established that the activity of the catalysts decreased in the following order: N-KAU > N-CNT > N-SKN > SKN > SKNо > KAUo-NH2 > CNT > catalase > KAU > CNTo > KAUо. It was shown that the catalytic activity of the samples did not correlate with structural parameters (surface area, pore volume), but depended on the nature of the surface chemistry of material (surface basicity and presence of quaternary nitrogen in the structure). Functionalization of carbon nanomaterials by oxygen heteroatoms decreases its catalytic activity while addition of nitrogen atoms increases their catalytic activity in the decomposition of lauroyl peroxide.